Impact of parasitic lifestyle and different types of centromere organization on chromosome and genome evolution in the plant genus Cuscuta - Neumann, Pavel; Oliveira, Ludmila; Čížková, Jana; Jang, Tae-Soo; Klemme, Sonja; Novák, Petr; Stelmach, Katarzyna; Koblížková, Andrea; Doležel, Jaroslav; Macas, Jiří (The New phytologist, 2021)
The parasitic genus Cuscuta (Convolvulaceae) is exceptional among plants with respect to centromere organization, including both monocentric and holocentric chromosomes, and substantial variation in genome size and chromosome number. We investigated 12 species representing the diversity of the genus in a phylogenetic context to reveal the molecular and evolutionary processes leading to diversification of their genomes. We measured genome sizes and investigated karyotypes and centromere organization using molecular cytogenetic techniques. We also performed low-pass whole genome sequencing and comparative analysis of repetitive DNA composition. A remarkable 102-fold variation in genome sizes (342-34 734 Mbp/1C) was detected for monocentric Cuscuta species, while genomes of holocentric species were of moderate sizes (533-1545 Mbp/1C). The genome size variation was primarily driven by the differential accumulation of LTR-retrotransposons and satellite DNA. The transition to holocentric chromosomes in the subgenus Cuscuta was associated with loss of histone H2A phosphorylation and elimination of centromeric retrotransposons. In addition, basic chromosome number of holocentric species (x = 7) was smaller than in monocentrics (x = 15 or 16). We demonstrated that the transition to holocentricity in Cuscuta was accompanied by significant changes in epigenetic marks, chromosome number and the repetitive DNA sequence composition.
Keywords: holocentric chromosomes; monocentric chromosomes; Convolvulaceae; Phylogeny; genome size; životní styl; molekulární evoluce; Evolution, Molecular; Genome, Plant; genom rostlinný; Life Style; centromera; centromere; repetitive DNA; Cuscuta; fylogeneze; Centromere